COMPUTER SUPPORT EXPERIMENTS IN TEACHING ELECTRICAL ENGINEERING - RADOCHA, Karol (Trends in education, 2014)
The article deals with the use of computers in conjunction with electrotechnical kit in teaching electrotechnical courses. Briefly summarizes the involvement of computer construction kit in a laboratory measurement or demonstration electrotechnical wiring circuits.
Keywords: Computer; Electrotechnical kit; RLC circuit.